Responsiveness of South African semi-commercial farmers to climate change - Maliba, Bheki (University of the Witwatersrand, Johannesburg, 2024)
Agriculture is crucial for sustaining rural livelihoods and promoting economic growth. However, climate change threatens agriculture as it is directly linked to climate factors. This study assesses how semi-commercial farmers are responding to climate change. The objectives were to (1) examine the perceptions of South Africa’s semi-commercial farmers on climate change; (2) assess the responsiveness of semi-commercial farmers to climate change; and (3) assess the influence of adaptation strategies on the performance of semi-commercial farmers. The data was collected through a self-administered questionnaire from 90 respondents and analysed. The demographic characteristics of the semi-commercial farmers were analysed using frequencies and descriptive statistics. In addition, a correlation analysis was conducted to determine relationships between different constructs, and multiple linear regression was used to model the relationship between variables. Most of the 90 respondents were 35 to 54 years old and had a high level of tertiary education (83.33%). The analysis of years in farming reveals a moderate experience level among participants, with 56.67% engaged in farming for 10-24 years. Rainfed agricultural practices dominated, with 57.78% relying solely on natural rainfall. Regarding access to credit, the mean score of 2.21 (standard deviation = 1.06) shows that, on average, respondents disagreed with the statements in the questionnaire about access to adequate credit, affordable lending rates, easy access to finance and alternative funding sources. Crop productivity indicated a positive correlation with soil and water conservation, and there was a positive correlation between changes in temperature and soil and water conservation. This suggests that their perception of temperature changes influences semi-commercial farmers' adaption strategies and that adopting climate strategies improves crop productivity. The study proved that soil and water conservation and crop diversification significantly predict crop productivity (performance). Recognising the positive correlation between soil and water conservation and crop diversification techniques and the perceived increased crop productivity, policymakers and agricultural extension services should prioritise and advocate for these strategies. Given the significant variations in respondents' access to credit, interventions should be tailored to the different financial needs of semi- commercial farmers. It is recommended that future research incorporate more comprehensive analyses of the development prospects of semi-commercial farmers, considering regional differences and assessing the long-term impact of adaptation strategies on actual agricultural production
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Adaptation strategies; semi-commercial farmers; climate change; performance; SDG-13: Climate action